2015
DOI: 10.1002/2015gl064957
|View full text |Cite
|
Sign up to set email alerts
|

Convergent crater circulations on Mars: Influence on the surface pressure cycle and the depth of the convective boundary layer

Abstract: Modeling of slope flow circulations in idealized axisymmetric craters is used to understand (1) the large surface pressure amplitude observed in Gale Crater by the Rover Environmental Monitoring Station and (2) the shallow convective boundary layer (CBL) suggested by Curiosity imagery. Air temperatures vary within craters with greater amplitudes than outside them, becoming warmer/colder during day/night. This crater circulation effect is most significant over the depth of the crater (key parameter). Within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 10 publications
4
38
0
Order By: Relevance
“…Boundary layer depth is more often presented in height coordinates (bottom row of Figure ), which displays a very similar pattern. Interestingly, this is almost the reverse of the spatial distribution noted in, e.g., Tyler and Barnes (), which focused on an earlier season: Ls~150°, the time of MSL's landing. While some observations have shown that PBL depth on Mars is larger where the pressure is lower, such as over high topography (e.g., Hinson et al, , ), the nature of the southern summer circulation at Gale Crater produces an inversion of this result.…”
Section: Vortex and Dust Devil Predictions Across Gale Crater Using Mmentioning
confidence: 64%
See 1 more Smart Citation
“…Boundary layer depth is more often presented in height coordinates (bottom row of Figure ), which displays a very similar pattern. Interestingly, this is almost the reverse of the spatial distribution noted in, e.g., Tyler and Barnes (), which focused on an earlier season: Ls~150°, the time of MSL's landing. While some observations have shown that PBL depth on Mars is larger where the pressure is lower, such as over high topography (e.g., Hinson et al, , ), the nature of the southern summer circulation at Gale Crater produces an inversion of this result.…”
Section: Vortex and Dust Devil Predictions Across Gale Crater Using Mmentioning
confidence: 64%
“…Unlike prior landing sites where dust devils have been studied, the Gale Crater site of the MSL mission has significant mesoscale topographic relief. While direct observations of circulation are limited to the MSL instruments, the nature of the circulation has been modeled by several different groups (Tyler & Barnes, , ; Rafkin et al, ; Pla‐Garcia et al, ; Newman et al, ; Fonseca et al, ; Richardson & Newman, ). The strong relief generates complex mesoscale circulations that interact both with the large‐scale flows commonly observed at other landing sites and with the microscale (PBL) circulation and structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tides observed by Curiosity are much larger than those simulated by global models, even when accounting for these tidal interactions. As such, various researchers have suggested further enhancements at the Curiosity site by crater circulations Tyler and Barnes 2015), topographic variations in the zonal band (Rafkin et al 2016), and a hydrostatic adjustment flow . Figure 4 shows the diurnal evolution of surface pressure at each landing site at L s = 145°, a seasonal date at which there is an overlap in data collected by all missions included in this study (Fig.…”
Section: Atmospheric Pressurementioning
confidence: 99%
“…We have already verified [Kite et al, 2013a], using the MarsWRF model [Toigo et al, 2012;Richardson et al, 2007], that the strongest winds are on the steepest slopes for a simulation of 1 year's winds at Gale crater. Here we use the Mars Regional Atmospheric Modeling System [Rafkin et al, 2001] to extend our earlier results through exploring a range of idealized topographies [Tyler and Barnes, 2015;. MRAMS is derived from the terrestrial RAMS model [Mahrer and Pielke, 1976].…”
Section: B1 Mesoscale Model Inputmentioning
confidence: 99%
“…Grid cells inside a canyon or crater are generally less windy than on the plateau surrounding the depression ( Figure B3). This is partly because the plateau is subject to the morning "surge" of air moving away from the canyon [Tyler and Barnes, 2015]. However, within the crater/canyon, wind stress is about 5 times greater for 15°slopes than for flat surfaces.…”
Section: B2 Mesoscale Model Outputmentioning
confidence: 99%